Sequences of errors in the Judo throw Morote Seoi Nage and their relationship to the learning process - Gutiérrez-Santiago, A.; Prieto, I.; Camerino, O.; Anguera, M. T. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2013)
The aim of this study was to identify the most common technical errors, and their behavioural sequences, in the judo throw Morote Seoi Nage. Participants (n = 46; 29 men and 17 women) were physical education students who were systematically observed by means of video recordings taken over a period of five academic years. The results, derived from descriptive statistics and a sequential analysis of T-patterns obtained with the software package THEME v.5, showed that a sub-optimal knee bend produces a throw around the side rather than over and towards the front of the shoulder. Furthermore, an inadequate hip and trunk position, caused by prior incorrect placement of the left foot, leads to a failure of weight bearing, which itself is the cause of the side throw. As regards the teaching and learning of judo, these findings enable us to propose motor drills to correct the errors detected, and movement sequences that will ensure a successful throw. Recommendations are also made about the use of feedback.